(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the specific characteristics of professional self-development skills of students studying in preschool education of higher educational institutions in the process of pedagogical practice. This, in turn, is of great importance in the development of this field. Development of targeted innovations based on the introduction of scientific innovations into the education system, increasing the effectiveness of training high-potential personnel, comprehensive support of students and young people are considered as urgent problems of today.